Now You See Me, Now You Don't: Environmental Conditions, Signaler Behavior, and Receiver Response Thresholds Interact to Determine the Efficacy of a Movement-Based Animal Signal - Bian, Xue; Chandler, Tom; Pinilla, Angela; Peters, Richard A. (Frontiers in Ecology and Evolution, 2019)
Knowledge of the environment in which animals operate and the sensory processing demands that mediate behavior in an ecological context are crucial for understanding animal communication systems. Understanding how environmental factors constrain communication strategies requires quantifying both the signal and noise in detail, as has been demonstrated in studies of acoustic and color signals for some time. However, comparable analyzes of movement-based animal signals and the signalling environment is limited. There is now growing evidence that the dynamics of motion noise, in the form of wind-blown plant-movement, are a major sensory constraint for movement-based signals. However, progress has been limited as traditional techniques for understanding the ecological constraints on movement-based signals have proven insufficient. Our study utilized an innovative approach to quantify motion ecology by simulating a signaling animal in a natural habitat using highly realistic 3D animations, which afforded us unprecedented control over the signal and the circumstances in which signalling takes place. Using the Jacky dragon Amphibolurus muricatus as a model species, we quantified the efficacy of signal in noise under different combinations of wind and dapple light intensities, and quantified the potential benefit of signaling faster, or in different orientations relative to the background. We also examined signal performance as a function of varying receiver operating characteristics. Our results suggest that prevailing environmental conditions at the time of signaling do indeed affect the efficacy of movement-based signals, with wind and light levels interacting to influence efficacy. We found that faster speeds and selecting particular orientations can be beneficial, but signal efficacy comes down to the interaction between wind conditions, intensity of dappled light, signaler orientation and thresholds for receiver responses.